Distrofia muscular progressiva: alguns aspectos do diagnõstico diferencial - Sylvio Saraiva; Aron J. Diament; José Antonio Levy (Arquivos de Neuro-Psiquiatria)
The authors call attention to some clinical entities which are less known and more difficult to recognize and with which differential diagnosis of progressive muscular dystrophy should be made (infantile spinal muscular atrophy, amyotonia congenita, congenital acute anterior poliomyelitis, anthro-griposis multiplex, von Gierke's disease, central core disease, chronical polymyositis and dermatomyositis, thyrotoxic myopathy and menopausal dys- trophy). The importance of muscle biopsy in the differential diagnosis is emphasized.